2017
DOI: 10.1093/mnras/stx1273
|View full text |Cite
|
Sign up to set email alerts
|

An automatic approach to exclude interlopers from asteroid families

Abstract: Asteroid families are valuable source of information to many asteroid-related researches, assuming a reliable list of their members could be obtained. However, as the number of known asteroids increases fast it becomes more and more difficult to obtain robust list of members of an asteroid family. Here we are proposing a new approach to deal with the problem, based on the well known Hierarchical Clustering Method (HCM). An additional step in the whole procedure is introduced in order to reduce a so-called chai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…We found that this catalogue contains colours of 55 family members. Based on this data, and following Radović, et al (2017), we were able to reliably identify only one potential interloper, the asteroid (38685) 2000 QP 9 . However, as this object was already marked as the interloper based on its albedo, no additional asteroid has been removed from the family based on the SDSS colours.…”
Section: Membership and Spectral Reflectance Characteristicsmentioning
confidence: 89%
“…We found that this catalogue contains colours of 55 family members. Based on this data, and following Radović, et al (2017), we were able to reliably identify only one potential interloper, the asteroid (38685) 2000 QP 9 . However, as this object was already marked as the interloper based on its albedo, no additional asteroid has been removed from the family based on the SDSS colours.…”
Section: Membership and Spectral Reflectance Characteristicsmentioning
confidence: 89%
“…First, we need a consistent way to identify asteroid family members for the training of the algorithms. For this purpose, we turn our attention to the data base of asteroid families available at the Asteroid Families Portal (AFP, http://asteroids.matf.bg.ac.rs/fam/properelements.php: accessed on 2019 December 5; Radović et al 2017). The web-page-based algorithms allow to automatically obtain asteroid families in a data set of 631 226 asteroids with synthetic proper elements using standard HCM procedures.…”
Section: Ac H I N E L E a R N I N G C L A S S I F I C At I O N O F mentioning
confidence: 99%
“…We required the chosen families to be represented in the Radović et al (2017) catalogue, to be located in the inner, central, and outer main belt at low inclinations (see Carruba et al 2013, for a definition of these zones), since in these regions, we found the most numerous families, and also to have at least 10 members with H < 14 (we include just one case with a lower sample, that of the Massalia family, so as to have a larger number of families located in the inner main belt. This family is most likely the outcome of a cratering event, which explains the lack of bright members; Milani et al 2019).…”
Section: Ac H I N E L E a R N I N G C L A S S I F I C At I O N O F mentioning
confidence: 99%
See 1 more Smart Citation
“…The inner and outer V-shapes must be wide enough to include enough asteroids in the inner V-shape and measure a N 2 in to N out ratio high enough to identify the family V-shape. The V-shape can include interlopers or asteroids which are not part of the family V-shape if the value used for dC is used is too large (Nesvorný et al 2015;Radović et al 2017). The V-shape identification technique was tested on families identified by both Nesvorný et al (2015) and Milani et al (2014) to verify that the V-shape a c , C and α determination works on family membership definitions from either database and produces similar results.…”
Section: V-shape Identification Technique and Measurement Of αmentioning
confidence: 99%